Ontogenetic Changes of the Aquatic Food Uptake Mode in the Danube Crested Newt (Triturus dobrogicus Kiritzescu 1903) - Natchev, Nikolay; Yordanova, Kristina; Topliceanu, Sebastian; Koynova, Teodora; Doichev, Dimitar; Cogălniceanu, Dan (Frontiers in Ecology and Evolution, 2021)
The study of the feeding mechanisms in vertebrates requires an integrative approach since the feeding event consists of a chain of behaviors. In the present study we investigated the food uptake behavior in different ontogenetic stages in the Danube crested newt (Triturus dobrogicus). We focused on the coordination in the kinematics of the elements of the locomotor and the feeding systems at the transition between the approach of the newt to the prey and the food uptake start. In both larvae and adult specimens, the animals approached the food to a close distance by a precise positioning of the snout besides the food item. The larvae were able to reach food items offered at over 80° relative to the longitudinal midline of the head. When the food was offered at a large distance or laterally, the food uptake was either not successful or the coordination chain at the transition between food approach and food uptake was interrupted. In young larvae we detected an abrupt change in the activity of the locomotor system and the feeding system. The larvae approached the food by tail undulation and after reaching the final position of attack, no further activity of the locomotor apparatus was detectable. The larvae used a pure form of inertial suction to ingest food. In pre-metamorphic larvae and adults we registered an integrated activation of the locomotor apparatus (both limbs and tail) and the feeding apparatus during prey capture in the form of compensatory suction. The drastic change in the feeding mode of the pre-metamorphotic larvae and the adult compared to the younger larvae in T. dobrogicus may indicates the evolutionary development of a defined relation in the activity of the locomotor system and the control of the feeding apparatus. We propose that in newts, the interaction between the control execution in both systems switched from successive (body movement - feeding) into integrated (body movement - body movement and feeding) during the ontogeny. The main trigger for such a switch (at least in T. dobrogicus) is the formation of functional limbs during the late larval development.